Sparta's Monumental Agenda: The Celebratory and Commemorative Monuments of Archaic and Classical Sparta - Thompson, Matt (2022)
This thesis examines Spartan celebratory and commemorative monuments of the Archaic and Classical periods based on the extant archaeological evidence and literary sources. The principal aim is to explore how the Spartans utilised monuments to project an image of themselves, in other words how the Spartans wished to be seen by their contemporaries and by future generations. The first two chapters set the framework for the study of monuments in relation to collective and cultural memory and summarise the current picture of Spartan culture in modern scholarship. Chapter 2 also examines Spartan self-presentation through a diachronic analysis of the terms ‘Spartiate’, ‘Lakedaimonian’, and ‘Lakonian’. Chapter 3 engages with the disparate evidence and interpretation of the Aigospotamoi Monument at Delphi, the Tomb of the Lakedaimonians in Athens, and the monuments potentially erected by Sparta to commemorate the Persian Wars. The evidence is then analysed thematically, in relation to artistic forms (Chapter 4), identity and distinction (Chapter 5), and place and memory (Chapter 6). These analyses reveal attempts, both by the state and individuals, to project a consistent image of strength and stability, but also tensions between influential individuals and groups and the state. This demonstrates that, in contrast to the traditional idea of the Spartan mirage whereby an identity was projected onto the Spartans by non-Spartan writers, the Spartans were actively involved in the creation and perpetuation of their image through monumental display.